Carex parva and Carex scabrirostris adopt diverse response strategies to adapt to low-light conditions - Liu, Wanting; Fan, Rong; Yang, Siyu; Chen, Sibo; Huang, Yulin; Ji, Wenli (Frontiers in Plant Science, 2024)
Introduction In recent years, the visible light intensity of lawns has significantly decreased due to obstructions caused by urban shading objects. Carex has a competitive advantage over other turfgrass in low-light conditions and extensive management. Therefore, exploring their survival strategy in low-light environments is of great significance. Methods This study focuses on two species of Carex, Carex parva and Carex scabrirostris, and investigates their response to low-light conditions (150 μmol/m2/s) by simulating urban lawn conditions. Biomass allocation characteristics, leaf anatomical features, biochemical parameters, root morphology and photosynthetic parameters were measured. Results (a) Peroxidase activity, specific leaf area, and relative water content are key factors influencing the photosynthetic capacity of the two Carex species. (b) Under low-light conditions, photosynthetic parameters, leaf physiological indicators, and biomass allocation of the two Carex species were significantly affected (p<0.05). Both Carex species increased their investment in leaf biomass, maintained lateral root growth, and cleared reactive oxygen species to maintain their physiological balance. (c) In the simulated urban low-light environment, neither C. parva nor C. scabrirostris produced dauciform roots. Discussion In terms of response strategies, C. scabrirostris is a high-photosynthesis investing species with high productivity under low-light conditions, whereas C. parva exhibits minimal response, indicating a slow investment. C. scabrirostris has greater potential for application in low-light environments compared to C. parva. These results provide a theoretical basis for the cultivation and application of these two Carex species, as well as the expansion of turfgrass germplasm resources.